Well being as health’s indicator - Muratori, Marcela (2025)
According to the World Health Organization, health is more than the absence of disease; it represents a state of complete physical, mental, and social well-being, tied closely to the enjoyment of fundamental human rights. Well-being can be understood through two traditions: the hedonic (which emphasizes happiness and the pursuit of pleasure), and the eudaemonic (which focuses on personal development and human potential). Another relevant dimension, the social well-being, evaluates societal functioning and support systems. Recent studies emphasize the importance of understanding well-being comprehensively rather than in fragmented perspectives. This study explored the different dimensions of well-being- subjective, eudaemonic, and social- among Argentine citizens. Results revealed generally high levels of subjective and eudaemonic well-being, with autonomy and personal growth standing out as key indicators, reflecting participants´ sense of independence and dedication to self-development. Life satisfaction and vitality were also high, though social well-being scored below the theoretical average, indicating negative assessments of societal functioning. Experienced well-being revealed a balance of positive and negative experiences, with a tendency toward enjoyment and satisfaction. Differences in well-being were observed across gender, age, marital status, and perceived social class. Notably, religious practice was associated with higher social well-being, though it also linked to increased negative affect. Despite limitations in sample size and scope, findings highlight the complexity of well-being and the need for comprehensive approaches to address social needs and promove effective interventions.